Comparative study of maximum respiratory pressure in adults from amazonas by different predictive equations - Silva, Cássio Daniel Araújo Da; Sanchez, Fernanda Figueirôa; Maciel, Maria Clara De Souza Pereira Gama; Figueira, Madria Andrade; Leon, Elisa Brosina De; Gonçalves, Roberta Lins (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: The measurement of muscular strength and maximum static pressures, substantially a consecrated and practical method, raise discussions about reference values and predictive equations, taking into account the heterogeneity of the studies. Objectives: Compare predicted values of IPmax and EPmax with the equations of Neder et al., 1999 and Costa et al., 2010 in adult individuals from the state of Amazonas (AM, Brazil). Method: A cross-sectional study in which was evaluated the Maximum Respiratory Pressures (IPmax and EPmax) according to standardization of the Brazilian Society of Pneumology and Tisiology in 210 individuals (68% female and 32% male) and 109 were eutrophic and 101 with overweight. The age of the individuals was 47,8±18,5 years. For comparative statistical analysis between the values obtained and predicted by the equations was performed the Anova One Way - Software SigmaStat 3.5 test. Results: The comparison of the values obtained with those predicted revealed that the Neder et al underestimated the IPmax in both genders (P <0,001) and overestimated the EPmáx in males (P <0,001). While the equation of Costa et al overestimated the IPmax and EPmáx in males (P <0,001) underestimated the IPmax in females (P<0,001). Conclusion: The results evidenced divergences in the predictive quality of the equations used, especially for IPmax, which suggests the low specificity of it in the population evaluated.